Optical imaging devices new technologies and applications - Khosla, Ajit; Kim, Dongsoo (Devices, circuits, and systems, 2016)
Optical Imaging Devices: New Technologies and Applications provides an essential understanding of the design, operation, and practical applications of optical imaging and sensing systems, making it a handy reference for students and practitioners alike